2009
DOI: 10.1073/pnas.0813327106
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed imaging of surface enhanced Raman scattering nanotags in living mice using noninvasive Raman spectroscopy

Abstract: Raman spectroscopy is a newly developed, noninvasive preclinical imaging technique that offers picomolar sensitivity and multiplexing capabilities to the field of molecular imaging. In this study, we demonstrate the ability of Raman spectroscopy to separate the spectral fingerprints of up to 10 different types of surface enhanced Raman scattering (SERS) nanoparticles in a living mouse after s.c. injection. Based on these spectral results, we simultaneously injected the five most intense and spectrally unique S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
670
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(674 citation statements)
references
References 35 publications
3
670
0
1
Order By: Relevance
“…Moreover, the detection sensitivity is limited by the small Raman scattering cross section (10 -29 -10 -32 cm 2 ) of endogenous biomolecules [5]. In contrast, surface-enhanced Raman scattering (SERS) technique can amplify Raman signals up to 10 14 folds using metallic surfaces [e.g., silver (Ag) and gold] [6]. The SERS strategy has also demonstrated in vivo Raman measurements with penetration deeper than 700 mm, but the subcutaneous injection of metal nanoparticles can be toxic [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the detection sensitivity is limited by the small Raman scattering cross section (10 -29 -10 -32 cm 2 ) of endogenous biomolecules [5]. In contrast, surface-enhanced Raman scattering (SERS) technique can amplify Raman signals up to 10 14 folds using metallic surfaces [e.g., silver (Ag) and gold] [6]. The SERS strategy has also demonstrated in vivo Raman measurements with penetration deeper than 700 mm, but the subcutaneous injection of metal nanoparticles can be toxic [7].…”
Section: Introductionmentioning
confidence: 99%
“…The second method uses a factor analysis algorithm to generate the component spectra, the weighted sum of which is compared to the Raman spectral data set. Using the latter of the two methods, Zavaleta et al demonstrated the power of the technique to quantify quantum dot accumulation in an in-vivo mouse model and to separate out the different spectral contributions from complex SERS signals in the same data set [91].…”
Section: Principal Components Analysismentioning
confidence: 99%
“…To detect diverse markers of neuronal lineage commitment simultaneously, nanomaterials emitting different optical signals might be combined with multiplex imaging techniques. Remarkable progress in the development of nanoparticles for in vitro multiplex analysis has made in vivo multiplex imaging more plausible [48][49][50].…”
Section: Requisites Of Multiplex Imagingmentioning
confidence: 99%
“…A recent study involving in vivo Raman spectroscopy [48] showed that ten different Raman signals could be separated from the signals acquired in vivo using [52] different types of SERS nanoprobes (120-nm particles) injected into subcutaneous sites. Simultaneous visualization of multiple nanoprobes with single imaging acquisition is therefore possible.…”
Section: Requisites Of Multiplex Imagingmentioning
confidence: 99%